The Effect of Collaborative Flipped Learning Strategy and Socio-cognitive Ability on Students’ Metacognitive Skills - Sukardi Abbas; Julkarnain Syawal; Tejapramuja Akun; Astuti Muh. Amin (Jurnal Penelitian Pendidikan IPA, 2022)
The reality shows that instructors and students are having difficulty implementing online science education during the pandemic. The purpose of this study was to determine the effect of collaborative flipped learning (CFL) strategy and socio-cognitive ability on metacognitive skills and self-efficacy in primary school pre-service teachers who were currently enrolled in a Basic Science course. This objective was motivated by the current state of education and teaching, which necessitates the use of technology to facilitate learning activities. This study employed a quasi-experimental design with a non-equivalent control group and a 2 x 2 MANOVA inferential statistical test. Prior to undertaking the inferential statistical test, we ran assumption tests, specifically normality and homogeneity analyses. The analysis results showed that there was a discrepancy in metacognitive skills between students in the experimental class who were taught the CFL strategy and those who were instructed the conventional strategy, indicated by an Fcalculated value of 11.299 and a significance value of 0.001. The analysis results also showed that there was a significant difference in metacognitive skills between students with high socio-cognitive ability and those with poor socio-cognitive ability, indicated by an Fcalculated value of 39.9724 and a significance value of 0.000. It was also found that the interaction between the learning strategy and socio-cognitive ability influenced students’ metacognitive skills. These findings suggest that educators should consider cognitive and social factors while implementing the collaborative flipped learning strategy to help students enhance their metacognitive skills